Transsexuals and The Ordination in The Theravada Buddhist - Chimpalee, Thanapon; Hemnalai, Asst.Prof Dr.Dechopol (Mahachula Academic Journal, 2024)
This article has the following objectives: (1) to study the types of gender from the perspective of Theravada Buddhism, (2) to study the goals of ordination from the perspective of Theravada Buddhism, (3) to study the conditions of ordination for both monks and nuns from the perspective of Theravada Buddhism, and (4) to analyze the feasibility of ordination for transgender individuals from the perspective of Theravada Buddhism. The research is conducted in four steps: (1) the researcher will gather information to understand the issue of gender types from the perspective of Theravada Buddhism, (2) the researcher will gather information to understand the goals of ordination from the perspective of Theravada Buddhism, (3) the researcher will conduct in-depth research to understand the conditions of ordination for both monks and nuns as stated in Theravada Buddhist scriptures, to show how these issues are explained, and (4) the final step is to analyze all the gathered information to determine whether transgender individuals can be ordained from the perspective of Theravada Buddhism and how this is explained. The research findings reveal tha it is found that the Abhidhamma Pitaka indicates that material qualities of sex i.e. femininity and masculinity, which are derivative materiality, are unchangeable so the process of sex change in transsexuals only changes the external body and the intrinsic gender characteristic cannot be changed. Thus, according to Buddhist scriptures, transsexuals cannot be ordained. Moreover, my view is that the ban of ordination for individuals with diverse sexual orientations stems from issues of gender inappropriateness and the potential problems of communal living, which could bring dishonor and shame within the Sangha. However, for transsexuals, after undergoing sex reassignment surgery, their physical and mental states are aligned so communal living issues within the Sangha would not arise. Finally, even though transsexuals are illegitimate, those who are considered incapable of achieving enlightenment, I would like to open a pathway for their ordination so that transsexuals can accumulate merit for attainment of the enlightenment in the future. They could also be contributors for propagating the Buddha's teachings and supporting maintenance of Buddhism in the future.